2013
DOI: 10.1109/tip.2013.2273669
|View full text |Cite
|
Sign up to set email alerts
|

3D Lacunarity in Multifractal Analysis of Breast Tumor Lesions in Dynamic Contrast-Enhanced Magnetic Resonance Imaging

Abstract: Dynamic contrast-enhanced magnetic resonance (DCE-MR) of the breast is especially robust for the diagnosis of cancer in high-risk women due to its high sensitivity. Its specificity may be, however, compromised since several benign masses take up contrast agent as malignant lesions do. In this paper, we propose a novel method of 3D multifractal analysis to characterize the spatial complexity (spatial arrangement of texture) of breast tumors at multiple scales. Self-similar properties are extracted from the esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…Computer extracted histogram-based image features have been shown to correlate with phenotypic heterogeneity. 15,16 We have also demonstrated that there are characteristics that are not readily appreciated visually but can be 22 have used fractal-based methods to extract data to characterize breast cancer spatial complexity. Finally, multiparametric MRI, which is helpful in distinguishing benign and malignant breast pathology, may also prove helpful in generating phenotypic biomarkers.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Computer extracted histogram-based image features have been shown to correlate with phenotypic heterogeneity. 15,16 We have also demonstrated that there are characteristics that are not readily appreciated visually but can be 22 have used fractal-based methods to extract data to characterize breast cancer spatial complexity. Finally, multiparametric MRI, which is helpful in distinguishing benign and malignant breast pathology, may also prove helpful in generating phenotypic biomarkers.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Ahmed et al 30 evaluated the ability of MRI textural analysis in predicting breast cancer response to chemotherapy and concluded that significant texture parameters and groupings were observed and differed between responders and nonresponders. Soares et al 22 have used fractal-based methods to extract data to characterize breast cancer spatial complexity. Finally, multiparametric MRI, which is helpful in distinguishing benign and malignant breast pathology, may also prove helpful in generating phenotypic biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lacunarity could also be used to quantify the severity of disease or to differentiate benign from malignant tumors. Literature presents various examples of the use of lacunarity in other scenarios, such as to assess osteoporosis [12], microvascular morphology [26], to analyze the behavior of prostate cancer [27] and breast tumor lesions [28], and to measure cell cancer behavior [29].…”
Section: Discussionmentioning
confidence: 99%